An important effect of filamentation instability on laser fusion physical processes. (14th February 2014) - Lin, Zunqi; Lei, Anle; Fan, Wei; Zhou, Shenlei; Wang, Li
Abstract The process of high power laser interaction with the large scale length corona plasma produced by the leading edge of the laser pulse has been investigated. Early experimental results are re-analyzed and conclusions drawn. In particular, studies of the close connection of unstable filamentation instability with – mainly – two-plasmon decay and – partly – stimulated Raman scattering, stimulated Brillouin scattering, and resonance absorption are carried out in this paper. The positive and negative effects of filamentation instability are also discussed.